The Screen for Child Anxiety-Related Emotional Disorders Is Sensitive but Not Specific in Identifying Anxiety in Children with High-Functioning Autism Spectrum Disorder: A Pilot Comparison to the Achenbach System of Empirically Based Assessment Scales - Lohr, W. David; Daniels, Katherine; Wiemken, Tim; Williams, P. Gail; Kelley, Robert R.; Kuravackel, Grace; Sears, Lonnie (Frontiers in Psychiatry, 2017)
Validated brief screening instruments are needed to improve the detection of anxiety disorders in autism spectrum disorder (ASD). The Screen for Child Anxiety Related Emotional Disorders (SCARED), a 41-item parent- and self-reported scale measuring anxiety, was compared to the Achenbach System of Empirically Based Assessment scales. One hundred participants with a clinical diagnosis of high functioning ASD, aged 8 to 18, and their parents completed the above scales. We hypothesized the SCARED would be useful in screening for anxiety and its results for total scores of anxiety would converge with ASEBA syndrome scales for anxiety and internalizing disorders. Significant correlations were shown between the SCARED and the Child Behavior Checklist (CBCL) and Youth Self-Report (YSR) across a broad spectrum of scales. The CBCL syndrome scale for anxious/depressed showed the highest correlation and predicted anxiety scores on the SCARED. While many of the YSR scales significantly correlated with child ratings of anxiety, none of the scales predicted the SCARED child scores. Differences in self and parent reports suggest that parents interpret externalizing behaviors as signs of anxiety in ASD, whereas youth may describe internalized symptoms as anxiety. Females were more likely to self-report anxiety than males. Results support the use of the SCARED as a screening tool for anxiety in high functioning ASD but it should be supplemented with other tools to increase the specificity of its results.